(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
PCR-ELISA (Enzyme-linkedlinked immunosorbent assay - polymerase chain reaction), immunodetection method used to count the PCR amplified creation just after the halt of biotinylated DNA on the microtiter bowl. Amplification, immobilization, and detection are the three phases of the synthesis chained response - enzymes coupled immunoassay assay procedure. PCR-ELISA is more sensitive than the conventional PCR method, it detects nucleic acids rather than protein with the lesser detection time and tinier analytical time. Due to its high sensitivity and specificity, it has potential application as a detection tool in the numerous industries like; agricultural, food industry, veterinary and medical. PCR-ELISA in industries used for the detection, diagnosis and quantitative monitoring.